Game-Based Learning Innovation in Elementary Physical Education: Development of Monopoly-Based PJOK Learning Media - Unorrizqo; Aprizal Fikri; Noviria Sukmawati; Muslimin (STKIP Pasundan, 2026)
This study aimed to develop a Monopoly-based learning medium for Physical Education, Sports, and Health (PJOK) for Grade V elementary school students and to examine its feasibility through expert validation. The study employed a Research and Development (R&D) approach guided by the ADDIE model, encompassing needs analysis, design, development, and expert validation stages. Needs analysis revealed limited use of instructional media in PJOK learning, resulting in low student engagement and weak conceptual understanding. The developed Monopoly-based media integrated cognitive, affective, and psychomotor learning components through theory-based questions, structured movement challenges, and collaborative gameplay. Expert validation involved a PJOK subject matter expert, a learning media expert, and a senior PJOK teacher. The validation results indicated high feasibility and content validity, supported by favorable CVR and CVI values. These findings suggest that the developed learning media is pedagogically sound and suitable for further field testing.